Graphical high level analysis of communication in distributed virtual reality applications - De Paiva Guimarães, Marcelo; Gnecco, Bruno Barberi; Dias, Diego Roberto Colombo; Brega, José Remo Ferreira [UNESP]; Trevelin, Luis Carlos (Elsevier, 2015)
Analysing distributed virtual reality applications communicating through message-passing is challenging. Their development is complex, and knowing if something is wrong depends on the states of each process, defects (bugs) cause software crashes, hangs, and generation of incorrect results. To address this daunting problem we specify functional behavior models (for example, using synchronization barriers and shared variables) for these applications that ensures correctness. We also developed the GTracer tool, which compares the functional behavior models developed with the messages transmitted among processes. GTracer checks for violations of these models automatically and displays the message traffic graphically. It is a tool made for libGlass, a message library for distributed computing. We have been able to find several non-trivial defects during the tests of this tool.
Keywords: Analysis; Bug; Defects; Distributed computing; Message passing; Virtual reality